PMO-189 Analysis of factors predictive of depth of insertion during double balloon enteroscopy. (28th May 2012) - Murino, A; Nakamura, M; Despott, E J; Fraser, C
Abstract : Introduction: For many decades the small bowel (SB) has represented a blind area for endoscopists, until the recent introduction of double balloon enteroscopy (DBE) allowing SB investigation and therapy. At times achieving deep insertion can be particularly challenging. The aim of this study was to determine factors that might influence depth of insertion during DBE. Methods: We retrospectively analysed 569 cases referred to our institute, a UK tertiary referral centre for DBE from February 2005 to October 2011. The maximum depth of insertion (MDI) was measured as described by May et al. History of abdomino-pelvic surgery, route of insertion, type of enteroscope, age, sedation or GA used and gender were considered influencing factors (IFs). Procedures were then divided into several subgroups according to the numbers IFs identified. Results: Out of 569 procedures reviewed, 399 cases were selected for this study (F:M=159:240, mean age: 56 years). The mean MDI was 212 cm. 274 procedures were approached via the oral route, P5 and T5 enteroscopes were used in 189 and 210 procedures respectively and 146 patients had a history of abdomino-pelvic surgery. MDI was significantly affected by history of surgery (p Conclusion: Our findings suggest that the MDI is significantly influenced by a history of abdomino-pelvic surgery, route of insertion and type of enteroscope used. Moreover the MDI tends to decrease if more than one factor is present. Based on these results, an estimation of likely insertion depth can be made prior to DBE and an appropriate strategy to achieve a successful outcome considered. Competing interests: A Murino: Grant/Research Support from: Research Grant in deep enteroscopy released by Imotec/Fujinon, M Nakamura: None declared, E Despott: None declared, C Fraser: None declared.